Potential Use of Coriander Waste as Fuel for the Generation of Electric Power - Rojas-Flores, Segundo (2023)
The increase in the population and its need to produce food has caused the level of contamination by organic waste to increase exponentially in recent years. Innovative methods have been proposed for the use of this waste and thus to mitigate its impact. One of these is to use it as fuel in microbial fuel cells to generate electricity. This research aims to generate bioelectricity using coriander waste in microbial fuel cells. The maximum voltage and current observed were 0.882 ± 0.154 V and 2.287 ± 0.072 mA on the seventh and tenth day, respectively, these values were obtained working at an optimum operating pH of 3.9 ± 0.16 and with an electrical conductivity of 160.42 ± 4.54 mS/cm. The internal resistance observed in the cells was 75.581 ± 5.892 Ω, with a power density of 304.325 ± 16.51 mW/cm2 at 5.06 A/cm2 current density. While the intensity of the final FTIR (Fourier transform infrared spectroscopy) spectrum peaks decreased compared to the initial one, likewise, with a percentage of identity, it was possible to attribute 98.97, 99.39, and 100% to the species Alcaligenes faecalis, Alcaligenes faecali, and Pseudomonas aeruginosa. Finally, the cells were connected in series, managing to turn on an LED light (red) with the 2.61 V generated. This research provides an innovative and environmentally friendly way that companies and farmers can use to reuse their waste.